STUDI SIMULASI TRANSPORTASI CAMPURAN ASPAL PANAS DAN ZONA LAYANAN ASPHALT MIXING PLANT - , M. Syamsul Hadi, Ir. Latif Budi Suparma, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Temperature of Hot Mix Asphalt (HMA) will decrease due to differential temperature with ambient temperature. If temperature decrease to lower than minimum compaction temperature, HMA will become less plastic and difficult to compacted. To minimize temperature decrease, HMA produced by Asphalt Mixing Plant (AMP) need to be transported to construction site immediately. Unit Pengolah Campuran Aspal (UPCA) Pasuruan is branch of Balai Besar Pelaksanaan Jalan Nasional (BBPJN) V Ministry of Public Works which has an AMP with 50 ton/hour in capacity. In term of technical consideration, it is necessary to conduct research to determine supplying coverage zone of UPCA Pasuruan. Equation of HMA decreasing temperature related to time when HMA leaving from AMP to construction site is created by regression of direct measurement of HMA temperatureâs data. Next step is creating simulation model of HMA spread and compaction work using EZ-Strobe. Model varied in spread wide and number of compaction vehicle used. Input program will comply with Panduan Analisa Harga Satuan (PAHS) Bina Marga 2010 and UPCA Pasuruan toolâs capacity except for input of speed, temperature decrease equation, and distance measurement. Simulation using Stroboscope is generated to determine supplying cooverage zone in national and province road. Temperature decrease equation of HMA Hot Rolled Sheet-Wearing Course (HRS-WC) in type which was produced when research is conducted is different depend on the dumptruck used. With HMA spread velocity equal to AMP production capacity, the longest coverage zone is achieved by HMA project with two effective compaction line in wide, using small truck, and 2 tandem rollers. The supplying coverage zone of national road is 64,6 kilometer start from district Jabon, region Sidoarjo to Probolinggo city with Ngopak market t-junction as midpoint. Supplying coverage zone of province road is 53,6 kilometer start from Wonorejo village and border of distric Rembang in west to border of district Lumbang and district of Tongas region Probolinggo with Winongan t-junction as midpoint.